Productivity, Stress, and Work-life Balance in the Remote Work Era: A study of Kathmandu Valley - Jha, Anish (SAIM Journal of Social Science and Technology, 2025)
Purpose: This study examines how working from home (WFH) affects employee productivity, stress, and work-life balance among employees in Kathmandu Valley, focusing on psychosocial and organizational factors that shape remote work experiences. Design/Methodology/Approach: Using an explanatory research design, data were collected from 409 remote employees via a structured Google Forms questionnaire through convenience sampling. Quantitative analysis employed Microsoft Excel for descriptive statistics and SmartPLS 4.0 to explore relationships between WFH, productivity, stress, and work-life balance. Findings: WFH improves work-life balance and lowers stress, which together boost productivity. However, employees face challenges including domestic distractions, lack of supervision, and communication issues. A strong preference for hybrid work models indicates the importance of flexible work arrangements. Conclusion: WFH can enhance productivity mainly by improving work-life balance and reducing stress, but addressing distractions and communication barriers is critical. Organizational support and effective digital infrastructure are necessary to maximize WFH benefits. Originality/value: This research provides unique empirical insights into WFH’s impact within Kathmandu Valley’s socio-cultural context, deepening understanding of remote work in developing economies.